Analysis of rare variants in the alcohol dependence candidate gene GATA4 - Degenhardt, Franziska; Witt, Stephanie; Mann, Karl; Kiefer, Falk; Spanagel, Rainer; Rietschel, Marcella (Alcoholism, 2016)
Background Common variants in the gene GATA binding protein 4 (GATA4) show association with alcohol dependence (AD). The aim of this study was to identify rare variants in GATA4 in order to elucidate the role of this gene in AD susceptibility. Identification of rare variants may provide a more complete picture of the allelic architecture at this risk locus. Methods Sanger sequencing of all 6 coding exons of GATA4 was performed in 528 patients and 517 controls. Four in silico prediction tools were used to determine the effect of a DNA variant on the amino acid sequence and protein function. Five variants were included in the replication step. Of these, 4 were successfully genotyped in our replication cohort of 655 patients and 1,501 controls. All patients fulfilled DSM-IV criteria for AD, and all individuals were of German descent. Results In the discovery step, 19 different heterozygous variants were identified. Four patient-specific and potentially functionally relevant variants were followed up. Only the variant S379S (c.1137C>T) remained patient specific (1/1,166 patients vs. 0/1,997 controls). None of the variants showed a statistically significant association with AD. Conclusions The present study elucidated the role of GATA4 in AD susceptibility by identifying rare variants via Sanger sequencing and subsequent replication. Although novel patient-specific rare variants of GATA4 were identified, none received support in the independent replication step. However, given previous robust findings of association with common variants, GATA4 remains a promising candidate gene for AD.